Hidden power: gender relations in export-oriented tasks and access to resources for Uganda's horticulture sector - Sengendo, May Christine (Gender Studies, 2023)
The aim of the study is to investigate gender relations in the production and export marketing of horticulture produce in Uganda. The study uses gender as an analytical tool in critiquing the Neoliberal reforms that advocate trade liberalization. This is done through examining the construction and perpetuation of unequal power relations within the tasks as well as access to production and market resources needed for effective participation in export trade. The study fills a gap in knowledge by providing an explanation of the factors that hinder effective participation of female and male tanners and traders. It reveals the failure of the assumptions of price, supply and demand as organizing principles in a market economy as those ignore the practices of politics and gender dynamics that shape the production and distribution of products for export trade. In order to reveal hidden control and influence of decisions, the study investigates the manifestation of power in the marketing channel at three sites: the household site (for production); the collection site (for purchase and assembling); and the exportation site (for export arrangements and air freight). Examples are given through a case study of female and male farmers, collectors and exporters of horticulture produce, in particular hot-pepper and okra, in Uganda. The unequal power relations that are examined, show how women and men create a hierarchical setting within the same site, as well as through the interactions they make by linking to the other sites. While female and male tanners require the tasks and resources provided by the collectors, collectors also need the resources given by exporters. Within such a context, this study, shows how gender analysis can be used to examine the dynamics of the relations between women and men who interact within tasks and resource acquisition between the different sites. The question of power therefore becomes a key concern as some categories of men, and sometimes women who are in positions of control of resources, have the "power to" influence decisions on allocation of tasks and acquisition of resources. Yet, such power to influence actions concerning who should perform the tasks and who can have access to resources, is so hidden that revealing it requires examination of its manifestations as well as the way its is exercised differently by men compared to women. Those practices, through which power manifests, create conflicts and hierarchical differences between tanners, collectors and exporters that show gender as well as status differences. Female collectors and exporters can manage to control resources, recognize these power practices, and react by resisting and manipulating them according to their own interests. Unfortunately, in most cases, both female and male tanners cannot challenge decisions of the exporters. Such dynamics create differential access to production and market resources. The characteristics that enable women as well as men to have influence are investigated in addition to what leads to the subordinate position that others experience. Gender theory is applied and focuses on two arguments: the extent to which men exercise power over women in ways that show how power relations are manifested through the gender division of labour and the way tasks are organised; and how power relations are manifested through different positions that women occupy compared to men in the different sites in ways that enable mostly men to have the power to influence decisions and command allocation of resources. Gender analysis is used as a methodology that enables examination of power practices that are hidden in the way tasks are organized and resources acquired in the different sites at a specified time period. Although these sites are self-contained, the findings indicate that actors also have opportunities to move across and between sites. The ability to participate in more than one site is therefore a means of rescue from practices that disempower women, thus hindering their participation in export trade. The findings do not only affirm the claims by gender critique of macro-economic theories that the markets are not abstract entities, but also provides examples that show how markets have a gendered structure. Women and men engage in relationships of cooperation, conflict and manipulate decisions of others who seek to access resources. Women who undertake activities in more than one site have power to make choices and influence decisions that would otherwise have had adverse effects on their export-oriented activities. Women who are able to access resources are sometimes those who exclude and exploit other women of lower status, just as higher-status men do to those below them. Such women decide to take actions not necessarily with an intention of resisting male dominance but to develop defensive and creative ways through which they can promote their own agenda. Some men of lower status resist actions of exploitation and exclusion imposed upon them by men of higher status. In addition, they can overcome the informality of labour provision and contracts that exist in trade relationships by becoming decision-makers themselves and dealing directly with export trade. This study therefore makes contributions to gender theory in ways that illustrate how gender analysis is an effective tool in investigating the construction of unequal power relations for export trade within an African setting.